EVALUASI KUALITAS INSTRUMEN TES MAHARAH QIRA’AH MENGGUNAKAN CLASSICAL TEST THEORY - Sri Wahyuni Hidayanti; Moch Fajarul Falah (Al Ibrah: Journal of Arabic Language Education, 2026)
This study is motivated by the importance of the quality of assessment instruments in measuring maharah qira’ah (reading comprehension skills) accurately and objectively. The study aims to evaluate the quality of a maharah qira’ah test instrument using the Classical Test Theory (CTT) approach through the analysis of item validity, reliability, difficulty level, and discrimination power. This research employed a descriptive quantitative method, with the object of study being a multiple-choice test instrument consisting of 10 items that had been used in Arabic language learning assessment. The data were obtained from the responses of 17 students from UIN Ar-Raniry and Syiah Kuala University who participated in maharah qira’ah learning at Dayah Darul Aman. Data analysis was conducted using IBM SPSS Statistics 22 through the Corrected Item-Total Correlation (CITC), Cronbach’s Alpha, item difficulty index, and item discrimination analysis. The results show that 8 items were valid and 2 items were invalid due to negative CITC values. The reliability coefficient of the instrument was 0.660, which falls into the moderate category. The analysis of item difficulty indicates that 8 items were categorized as easy and 2 items as moderate. Meanwhile, the discrimination index results show that most items were in the good category; however, 2 items had negative discrimination power. The study concludes that the maharah qira’ah test instrument has a fairly good quality, but still requires revision on several items to improve its validity and reliability. The findings indicate that the quality of an assessment instrument is not only determined by the number of valid items, but also by the balance of indicators, the quality of item construction, and the appropriateness of cognitive levels being measured. This study contributes empirical evidence on the importance of item analysis before instruments are used in Arabic language assessment, in order to improve the accuracy of measuring students’ reading comprehension skills. Abstrak Penelitian ini dilatarbelakangi oleh pentingnya kualitas instrumen evaluasi dalam mengukur kemampuan maharah qira’ah secara akurat dan objektif. Penelitian bertujuan untuk mengevaluasi kualitas instrumen tes maharah qira’ah menggunakan pendekatan Classical Test Theory (CTT) melalui analisis validitas, reliabilitas, tingkat kesukaran, dan daya pembeda butir soal. Penelitian ini menggunakan metode deskriptif kuantitatif dengan objek penelitian berupa instrumen tes pilihan ganda sebanyak 10 butir soal yang telah digunakan dalam evaluasi pembelajaran bahasa Arab. Data penelitian diperoleh dari hasil jawaban 17 mahasiswa UIN Ar-Raniry dan Universitas Syiah Kuala yang mengikuti pembelajaran maharah qira’ah di Dayah Darul Aman. Analisis data dilakukan menggunakan IBM SPSS Statistics 22 melalui uji Corrected Item-Total Correlation (CITC), Cronbach Alpha, indeks kesukaran, dan daya pembeda butir soal. Hasil penelitian menunjukkan bahwa terdapat 8 butir soal valid dan 2 butir soal tidak valid karena memiliki nilai CITC negatif. Nilai reliabilitas instrumen memperoleh Cronbach Alpha sebesar 0,660 yang berada pada kategori cukup. Analisis tingkat kesukaran menunjukkan 8 butir soal berada pada kategori mudah dan 2 butir soal berada pada kategori sedang. Sementara itu, hasil daya pembeda menunjukkan sebagian besar butir soal berkategori baik, namun terdapat 2 butir soal dengan daya pembeda negatif. Penelitian ini menyimpulkan bahwa instrumen tes maharah qira’ah memiliki kualitas yang cukup baik, namun masih memerlukan revisi pada beberapa butir soal agar lebih valid dan reliabel. Temuan penelitian menunjukkan bahwa kualitas instrumen tidak hanya ditentukan oleh jumlah butir soal yang valid, tetapi juga oleh keseimbangan indikator, kualitas konstruksi soal, serta kesesuaian tingkat kognitif yang diukur. Kontribusi penelitian ini memberikan informasi empiris mengenai pentingnya analisis butir soal sebelum instrumen digunakan dalam evaluasi pembelajaran bahasa Arab sehingga dapat meningkatkan kualitas pengukuran kemampuan membaca peserta didik.